Kesiapan Implementasi Knowledge Sharing & Transfer (KS&T) dalam pembelajaran di Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Arief, Mochamad Budi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Higher education as a sub-system of the national education system has a strategic role that includes educating the nation's life and advancing science and technology. Universities as an institution that has a strategic role in achieving a generation of excellence and quality in the development of Science and Technology, so as to compete in the global era and digital today. The purpose of this research is: to describe readiness implementation of Knowledge Sharing & Transfer (KS & T) in learning at Tarbiyah High School of Raden Wijaya Mojokerto. This research uses